TINJAUAN PROSES PEMBUATAN ALAT MUSIK GESEK BETAWI KONGAHYAN - Imam Firmansyah; Faisal Ibrahim; Irgi Maulana Alfahrezy (Narada : Jurnal Desain dan Seni, 2020)
Kongahyan is a Betawi stringed instrument that has an important function in the gambang kromong ensemble, as a bearer of melody. This musical instruments are made of wood and coconut shells. It’s made by craftsmen who are also players of the gambang kromong. But the existence of kongahyan craftsmen is very rare. There are only two persons in Jakarta and one in Tangerang. This condition is very alarming because it does not rule out the possibility of this musical instrument will become extinct due to the limitations of the maker. The research method used is a qualitative research method with a descriptive approach that is to present data by observing, studying, and documenting the process of making a kongahyan. This research found that kongahyan consisted of three major parts, namely stem, coconut shell, and bow. The three major parts are then assembled into one unit. The results of this research can be used as a reference both theoretically and practically regarding the process of making kongahyan musical instruments. In addition, this research paper is also complemented with a comprehensive documentation of the manufacturing process.